ANALISIS FAKTOR-FAKTOR BAURAN PEMASARAN (7P) YANG MEMPENGARUHI KEPUTUSAN PELAKU USAHA UMKM DALAM PEMILIHAN PENGAJUAN KREDIT PADA BANK DI DAERAH ISTIMEWA YOGYAKARTA - Ahsan Sumantika; Faizal Ardiyanto (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2017)
Abstract This research aimed to test the influence of factors in marketing mix which consist of product, price, place, promotion, people, physical evidence, and process toward the loan selection decision by SME businessmen in Yogyakarta Special Region bank. The sampling method is purposive sampling with 99 respondents. Multiple regression analysis is utilized to test the hypotheses. The testing result shows that there are 2 variables : product and physical evidence, significantly which is positively influence dependent variable. However, price, place, promotion, people, and process do not have significance influence towards dependent variable. Keywords: SME, product, price, place, promotion, people, physical evidence, process, and marketing mix